THE POSITION OF ENVIRONMENTAL ACCOUNTING IN IMPROVING THE SUSTAINABILITY CAPACITY OF COMPANIES IN INDONESIA - Muhamad Rizki Putrangga Septiawansyah; Trinanda Julia Putri; Yuda Mochamad Sopian (Antis Publisher, 2024)
This paper aims to examine the role of environmental accounting in enhancing the sustainability capacity of companies in Indonesia. Using a literature review methodology, this study analyzes secondary data from previous studies conducted between 2016 and 2024. Environmental accounting, which includes the identification, measurement, evaluation and disclosure of costs associated with a company's environmental operations, is increasingly recognized as essential for regulatory compliance and operational efficiency. Findings show that companies adopting environmental accounting practices benefit from improved resource management, reduced costs through energy efficiency and waste management, and enhanced reputation among stakeholders. In addition, the integration of social and environmental responsibility into business strategies is aligned with sustainable development goals, thus ensuring the long-term viability of companies. This study underscores the importance of transparent environmental reporting and strategic decision-making facilitated by accurate environmental information. This paper highlights the importance of transparent environmental reporting and strategic decision-making facilitated by accurate environmental information. A comprehensive review of the existing literature highlights the important function of environmental accounting in promoting sustainable economic growth and maintaining ecological balance within the corporate sector in Indonesia.